Fluency and complexity as coupled growers in speaking English at secondary school – A case study of a good, average, and poor language learner - Katarzyna Joanna Rokoszewska (LingBaW)
One of the main assumptions of Complex Dynamic Systems Theory (CDST) is that internally complex language subsystems develop non-linearly while entering different kinds of supportive, competitive, conditional, or dual relationships which are characterised by trade-offs caused by learners’ restricted cognitive processing, especially in foreign language speech. The present paper belongs to a short series of articles which examines various aspects of the development of L2 English speech at secondary school on basis of the same longitudinal, exploratory, and corpus-based case study. The aim of this paper is to investigate the dynamics of the relationships between fluency and both syntactic and lexical complexity in the speech of a good, average, and poor language learner at the level of secondary school. Syntactic complexity was investigated in terms of general sentence complexity, subordination, coordination, and nominalisation, whereas lexical complexity was construed in terms of lexical density, sophistication, and variation. In general, the results indicated predominantly supportive relationships between fluency and different measures of syntactic complexity but competitive or dual relationships between fluency and lexical complexity. However, the relationships between the selected variables fluctuated over time and often differed in the case of a good, average, and poor language learner.